Optimization Of Passport Issuance Rules For Prospective Indonesian Migrant Workers In The Formal Sector (Case Study In Class I Immigration Office Non-Tpi Tangerang) - Dino Fahrenzky; Anita Herlina (Journal of Law and Border Protection, 2022)
The high number of unemployed in the Tangerang area and the increased demand forincreasedonesian Migrant workers from the count having a cooperation contract with the Indonesian side that people are willing to become PMI with the auto. Types of Indonesian Migrant Workers in the formal sector are classified into the types of Indonesian Migrant Workers who work for employers who are legal entities. The rules governing passport issuance requirements for prospective Indonesian migrant workers are regulated in the Minister of Law and Human Rights Regulation Number 8 of 2014 concerning Ordinary Passports and Travel Letters. Like PassportsA recommendation letter for issuing passports from the Manpower Office is one requirequirementgiving ta ticket fovisato stive, Indonesian migrant workers. Still, in its implementation at the Immigration Office Class I NoNon-Non-TPIgerangrospective, Indonesian migrant workers, especially in the formal sector, often do not take care of issuing recommendation letters for issuing passports from the Manpower Office for various reasons. Therefore, it is explained that the implementation of regulations for PMI candidates who register for passport issuance at the Class I Non-TPI Tangerang Immigration Office is explained whether the rules for PMI candidates in the formal sector are optimal. Therefore, it is necessary to optimize the laws governing the requirements for issuing passports for prospective Indonesian migrant workers, especially in the illegal industry, whiwhiwhicis optimal. This can be seen from the immigration system at the time of data entry; only prospective migrant workers in the informal sector are required to input PMI ID, while profuturedonesian migrant workers in the formal sector do not enter PMI I, D so the data entry process can continue. Thereforeurgente copy of the recommendation letter for passport issuance from the Manpower Office is only focused on prospective Indonesian migrant workers in the informal sector, not on prospfuturenesian migrant workers in the formal sector.